The Body as Territory - Ramirez Salgado, Amira Ixchel (2024)
This article presents a fragment of the findings obtained as part of a practice-research process in dance, focusing on the theme of Body and Territory. The concept and metaphor of the body as territory are introduced as a dynamic framework that emerges from the interplay of physicality, thought, memory, and sensitivity. Through movement-based workshops, which form part of the research methodology, the moving body is mapped and witnessed, revealing its poetic, sensory, and narrative dimensions. Moreover, drawing on Latin American and feminist epistemologies, the concept of territory is approached from a relational perspective rather than as a closed, one-dimensional definition. Building on these reflections, the notion of "felt territory" is explored, which implies a distancing from individual identity, allowing the body to be affected and move towards a collective sense. In this process, the political, social, and cultural dimensions of these delineations of the body-territory are recognized. Finally, through the testimonies of participants from one of the workshops discussed in this article, a conceptual and methodological framework is proposed to define the body as territory, enabling it to be inhabited through a movement-based experience.